2021
DOI: 10.1038/s41440-021-00769-0
|View full text |Cite
|
Sign up to set email alerts
|

Blood pressure, frailty status, and all-cause mortality in elderly hypertensives; The Nambu Cohort Study

Abstract: Antihypertensive therapy is pivotal for reducing cardiovascular events. The 2019 Guidelines for the Management of Hypertension set a target blood pressure (BP) of <140/90 mmHg for persons older than 75 years of age. Optimal BP levels for older persons with frailty, however, are controversial because evidence for the relationship between BP level and prognosis by frailty status is limited. Here, we evaluated the relationship between systolic BP and frailty status with all-cause mortality in ambulatory older … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…To date, few studies have analysed the prevalence of frailty in older patients with hypertension, providing highly variable proportions ranging from 3 to 68% according to the clinical setting and the adopted assessment tool [ 9 , 45 , 46 ]. In older adults participating in the HYVET and SPRINT studies, frailty status was identified using the FI and a left skewed distribution of scores was observed, with median values of 0.17 and 0.18, respectively [ 12 , 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…To date, few studies have analysed the prevalence of frailty in older patients with hypertension, providing highly variable proportions ranging from 3 to 68% according to the clinical setting and the adopted assessment tool [ 9 , 45 , 46 ]. In older adults participating in the HYVET and SPRINT studies, frailty status was identified using the FI and a left skewed distribution of scores was observed, with median values of 0.17 and 0.18, respectively [ 12 , 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis of observational studies showed that the blood pressure less than 140 is associated with lower mortality in non-frail patients, but the association was not observed in frail patients with 1.02 of hazard ratio 14 . In 535 older hypertensive patients in a Japanese cohort study, mortality rates stratified by systolic BP and frailty status were the lowest in patients with systolic BP < 140 mmHg and non-frailty, followed by those with systolic BP ≥ 140 mmHg and non-frailty 15 . In contrast, patients with frailty had the highest mortality regardless of the BP level, suggesting that frail patients have a poor prognosis regardless of their BP levels 15 .…”
Section: Difference In the Significance Of Intensive Hypertension Tre...mentioning
confidence: 97%
“…In 535 older hypertensive patients in a Japanese cohort study, mortality rates stratified by systolic BP and frailty status were the lowest in patients with systolic BP < 140 mmHg and non-frailty, followed by those with systolic BP ≥ 140 mmHg and non-frailty 15 . In contrast, patients with frailty had the highest mortality regardless of the BP level, suggesting that frail patients have a poor prognosis regardless of their BP levels 15 . A recent study showed the association between systolic BP and mortality in older adults with or without frailty determined by frailty index 16 .…”
Section: Difference In the Significance Of Intensive Hypertension Tre...mentioning
confidence: 97%
“…In the same cohort, patients were prospectively followed up for 41 months and the associations of mortality with frailty and BP were evaluated. Among 49 patients who died, mortality rates were lowest in those with systolic BP < 140 mmHg and non-frailty, and highest in those with systolic BP < 140 mmHg and frailty [ 10 ]. The results indicated that frail patients have a higher risk of all-cause mortality than non-frail patients, especially those with lower BP, suggesting that frailty should be taken into account during BP management.…”
Section: Frailty and Blood Pressure Targetsmentioning
confidence: 99%